(untitled) (American Journal of Pedagogical and Educational Research, 2024)
The article considers the concept of Happiness/Baxt in the English and Uzbek linguistic cultures as one of the most important universal concepts with a national component. On the one hand, the study is conditioned by the interest of modern contrastive linguistics in the comparative research of concepts with a national component. On the other hand, it continues scientific works concerned with the concept of happiness in the English linguistic culture and the concept of Baxt in the Uzbek linguistic culture.